Re-irradiation for recurrent and second primary cancers of the head and neck. (April 2017) - Velez, Maria A.; Veruttipong, Darlene; Wang, Pin-Chieh; Chin, Robert; Beron, Philip; Abemayor, Elliot; St. John, Maie; Chen, Allen M.
Highlights: Re-irradiation for recurrent and new primary head and neck cancer is feasible and effective in carefully selected patients. The high observed rate of treatment-related morbidity highlights the continue challenges that accompany this approach. Abstract: Purpose: To evaluate a single-institutional experience with the use of re-irradiation for recurrent and new primary cancers of the head and neck. Methods: The medical charts of 80 consecutive patients who underwent re-irradiation for local-regionally recurrent or second primary head and neck cancer between November 1998 and December 2015 were analyzed. Multivariate analysis was performed using Cox proportional hazard and logistic regression to determine predictors of clinical outcomes. Results: Seventy-six of the 80 patients were evaluable. The median age was 57.5 (range 26.6–84.9); Intensity-modulated radiotherapy (IMRT) was used in 71 (93.4%) patients with a median dose of 60 Gy. Thirty-one patients (40.8%) underwent salvage surgery before re-irradiation and 47 (61.8%) received concurrent systemic therapy. The median time interval between radiation courses was 25.3 months (range 2–322 months). The 2-year estimates of overall survival, progression free survival, locoregional control, and distant control were 51.0%, 31.3%, 36.8% and 68.3%, respectively. Patients who underwent salvage surgery prior to re-irradiation had significantly improved locoregional control, progression free survival, and overall survival (p < 0.05, for all). On multivariate analysis, gross tumor volume (GTV) at re-irradiation and interval between radiation courses were associated with improved overall survival. Severe (grade ⩾ 3) late complications were observed in 25 patients (32.8%). Conclusions: Re-irradiation for recurrent or second primary head and neck cancer is feasible and effective in select patients with head and neck cancer. The high observed rate of treatment-related morbidity highlights the continue challenges that accompany this approach.